Examining the dominance of Comprehensive Income to Net Income as a Measure of Firm Performance - KANWAL, RANI SHAISTA; NAWAZ, MUHAMMAD ATIF; YOUSAF, WASEEM; HUSSAIN, MUHAMMED SAJJAD; RIAZ, MADIHA (The journal of contemporary issues in business and government, 2021)
In this study we examine the relative ability of comprehensive income and net income to summarize firm performance as reflected in stock returns. We also examine which comprehensive income adjustments get better the aptitude of income to summarize firm performance. We also examine this claim that income measured on a comprehensive basis is a better measure of firm performance than other summary income measures. The results do not show that comprehensive income is superior to net income for evaluating firm performance on the basis of stock return and price. Except for investment industrial group, In Tehran Stock Exchange, we found no evidence that comprehensive income for firm performance evaluation on the basis of cash flows prediction is superior to net income. While, we found the better results for the state companies (only in other companies group), i.e., firm performance evaluation on the basis of cash flows prediction using comprehensive income is superior to net income. Collectively, our results provide some weak evidence that show comprehensive income adjustments improve ability of income for reflecting firm performance.